Standard Liver Volume-Predicting Formulae Derived From Normal Liver Volume in Children Under 18 Years of Age - Yang, Xintian; Wang, Han; Dong, Bingzi; Hu, Bin; Hao, Xiwei; Chen, Xin; Zhao, Jing; Dong, Qian; Zhu, Chengzhan (Frontiers in Pediatrics, 2021)
Background Standard liver volume (SLV) is important in risk assessment for major hepatectomy. We aimed to investigate the growth patterns of normal liver volume with age and body weight (BW) and summarized formulae for calculating SLV in children. Methods Overall, 792 Chinese children (<18 years of age) with normal liver were enrolled. Liver volumes were measured using computed tomography. Correlations between liver volume and BW, body height (BH), and body surface area (BSA) were analyzed. New SLV formulae were selected from different regression models; they were assessed for multicentral validations and were compared. Results The growth patterns of liver volume with age (1 day–18 years) and BW (2–78 kg) were summarized. The volume grows from a median of 139 ml (111.5–153.6 in newborn) to 1180.5 ml (1043–1303.1 at 16–18 years). Liver volume was significantly correlated with BW (r=0.95, P<0.001), BH (r=0.92, P<0.001), and BSA (r=0.96, P<0.001). The effect of sex on liver volume increases with BW, and BW of 20 kg was identified as the optimal cutoff value. The recommended SLV formulae were BW≤20 kg: SLV=707.12×BSA1.09; BW>20 kg, males: SLV=691.90×BSA1.06; females: SLV=663.19×BSA1.04. Conclusions We summarized the growth patterns of liver volume and provided formulae predicting SLV in Chinese children, which is useful in assessing the safety of major hepatectomies.